De cartas e de poesia: o projeto poético de Manuel Bandeira - Coelho, Gládiston de Souza (2013)
The aim of this research is the analysis of the genesis of Manuel Bandeira s poetic project by the letters exchanged between him and Mário de Andrade. And, thus the readings, analyses and comparisons of his poetry, see how the poet constitutes his lyric. Initiated in May 1922 and prolonged until October 1944, these letters show elements of poetic project of Bandeira. In the epistolary discourses, are recorded the dialogues that underpin much from the poet s thoughts. Considering this, it delineates the key question of this survey, that is, checking how far the facts discussed by the poet in his letters are effectively applied in his verses. The analyzed corpus is consisted by letters of the two interlocutors and the poems of Manuel Bandeira. The methodology of the analysis goes from comparisons of speeches to observing the more incisive and points that offer the necessary elements for investigation in the processes of creation. As a theoretical framework for understanding the historicity, social context and life and work of Bandeira, we support in studies of Antonio Candido, Lafetá, Julio Castañon and Alfredo Bosi. About the studies of letters and the processes of creation, we resorted to Hansen, Moraes and Salles. The part about the concepts of music, the study is based on the concepts of Bennett, Carpeaux, Chissel, Golden, Med, Priolli, Schafer and Schoenberg. Finally, the results lead us to understand the letter like fragments of memory residue and multifaceted discourse that reveals the creative process of the poetics of Manuel Bandeira as one of the proposals of the turn